2015
DOI: 10.1177/0739986315578842
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Trauma Among Caregivers Who Work With Mexican and Central American Refugees

Abstract: Thousands of refugees have fled Mexico, Honduras, Guatemala, and El Salvador to escape violence, criminal victimization, and persecution as a result of the breakdown of public safety that has accompanied the rise of organized crime and drug-related violence. Many of these migrants have experienced torture, rape, abduction, forced labor, arson, and kidnapping. Caregivers and professionals who work with these refugees, including social workers, volunteers, attorneys, and advocates, have repeatedly witnessed seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 26 publications
(35 reference statements)
7
83
1
2
Order By: Relevance
“…The top 3 types of traumatic births described by the CNMs were fetal demise/neonatal death, shoulder dystocia, and infant resuscitation. Our findings of STS was higher that found in Lusk and Sam Terrazas a study of 31 professionals and para-professionals who work directly with refugees in various settings [25], including legal aid offices and counseling centers in United States to address the challenge of coping with traumatized clients showed that 30% of the respondents scored in the severe to high range on the STS. Our study showed that there were statistically significant differences in secondary traumatic stress according to sex toward male professionals.…”
Section: Discussioncontrasting
confidence: 41%
“…The top 3 types of traumatic births described by the CNMs were fetal demise/neonatal death, shoulder dystocia, and infant resuscitation. Our findings of STS was higher that found in Lusk and Sam Terrazas a study of 31 professionals and para-professionals who work directly with refugees in various settings [25], including legal aid offices and counseling centers in United States to address the challenge of coping with traumatized clients showed that 30% of the respondents scored in the severe to high range on the STS. Our study showed that there were statistically significant differences in secondary traumatic stress according to sex toward male professionals.…”
Section: Discussioncontrasting
confidence: 41%
“…In a cross‐sectional survey of service providers for the homeless population, 65% believed that their work positively influenced people's lives, and 83% felt at least moderately successful in their work with clients (Hagen & Hutchison, ). Similarly, among caregivers working with refugees, all participants reported being proud of their work and 90% gained satisfaction from helping people (Lusk & Terrazas, ). Two studies found that seeing change in refugees and homeless individuals and receiving their gratitude was most rewarding to staff in social work (Guhan & Liebling‐Kalifani, ; Kidd et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies in the refugee sector and three studies in the homeless sector identified encountering clients' suffering and regularly hearing clients' stories and traumatic experiences as a major demand (Ferris et al, ; Grimm et al, ; Guhan & Liebling‐Kalifani, ; Kidd et al, ; Kosny & Eakin, ; Lusk & Terrazas, ; Robinson, ). The inability to change the situation of their clients or the little success staff experience in their work were also frequently reported (Chapleau et al, ; Kidd et al, ; Lusk & Terrazas, ; Robinson, ; Sutton‐Brock, ). Furthermore, ethical questions played a role: in one study, staff members of a refugee centre experienced distress caused by moral dilemmas in situations in which they became aware of unlawful behaviour of their clients (Guhan & Liebling‐Kalifani, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations